Postoperative Analgesic Requirement and Pain Perceptions after Nonaerodigestive Head and Neck Surgery. (December 2019) - Stephenson, Elizabeth D.; Farzal, Zainab; Jowza, Maryam; Hackman, Trevor; Zanation, Adam; Du, Eugenie
Objectives: Little data exist on associations between patient factors and postoperative analgesic requirement after head and neck (H&N) surgeries. Such information is important for optimizing postoperative care considering concerns regarding opioid misuse. We analyzed factors associated with narcotic use and pain perception following H&N surgery sparing the upper aerodigestive tract. Study Design: Prospective cohort. Setting: Tertiary referral center. Subjects and Methods: From May to October 2017, data were collected for patients undergoing nonaerodigestive H&N procedures requiring hospitalization. Patients completed a preoperative survey querying chronic pain history, narcotic usage, and postoperative pain expectation. Demographics, surgical data, postoperative narcotic use defined by morphine milligram equivalents (MME), pain scores, and Overall Benefit of Analgesia Score (OBAS) were analyzed. Results: Seventy-six patients, 44 (57.9%) females and 32 (42.1%) males with a mean age of 54.0 years, met inclusion criteria. The most common procedures were parotidectomy (27.6%) and total thyroidectomy (19.7%). Average cumulative 24-hour postoperative MME and calculated MME per hospital day (MME/HD, cumulative MME for hospitalization divided by length of stay) were 40.5 ± 30.6 and 60.8 ± 60.1, respectively. Average pain score throughout the initial 24 hours after surgery was 3.7/10 ± 2.0. Female sex and prior chronic pain diagnosis were associated with higher OBAS after multivariate linear adjustments. Conclusion: Postoperative narcotic requirement in nonaerodigestive H&N surgery is overall low. Female sex and prior chronic pain diagnosis may be associated with higher postoperative OBAS, a validated assessment of pain and opioid-related side effects. This study may serve as a comparison for future studies evaluating narcotic-sparing analgesia and pain perception in nonaerodigestive H&N surgery.